Use of Vasavital® in patients with diabetic retinopathy - Khramenko, N. I.; Umanets, M. M.; Medvedovska, N. V.; Levytska, G. V.; Rozanova, Z. A. (Ukrainian Journal of Ophthalmology, 2025)
Background: Diabetic retinopathy (DR) is a major cause of visual impairment or blindness among working-age adults worldwide. For years, researchers around the world have been trying to develop new effective pharmaceutical methods of treatment for preclinical and early DR. Purpose: To examine the effect of a one-month course of Vasavital on the function of the visual system and ocular hemodynamics (using ophthalmic rheography) in patients with non-proliferative and proliferative diabetic retinopathy (NPDR and PPDR, respectively). Material and Methods: Forty-seven type 2 diabetes patients with DR and moderate glycemic control were divided into those with NPDR (group 1 of 15 patients; 30 eyes) and those with PPDR (group 2 of 17 patients; 34 eyes). The control group was composed of 15 volunteers (30 eyes) of similar age having no systemic or eye disease. Patients received a one-month course of Vasavital-only therapy at a dose of one capsule twice a day as an outpatient treatment. They received visual acuity assessment, intraocular pressure measurement, ophthalmoscopy, biomicroscopy, perimetry, systemic blood pressure and pulse measurement, optical coherence tomography and fluorescein angiography, and ocular hemodynamics was assessed by ophthalmic rheography. Eleven patients (22 eyes) with NPDR and ten patients (20 eyes) with PPDR underwent electrophysiological studies of electrically evoked phosphene threshold (EEPT) and critical frequency of phosphene disappearance (CFPD), before and after a course of Vasavital treatment. Results: Patients reported that a one-month course of Vasavital was well-tolerated, with no new complaints. In addition, no side effects were observed. After treatment, the function of the photopic afferent system as assessed by light sensitivity at minutes 0 to 7 of adaptation improved by 33.3%-40% in patients with NPDR and by 27.2%-33.3% in patients with PPDR. In addition, there was a decrease in EEPT by 18% and 7.7%, respectively, and an increase in CFPD by 28.2% and 24.7%, respectively, for patients in groups 1 and 2. Moreover, ocular pulse blood filling improved by 27.7% in patients with NPDR and by 17.3% in patients with PPDR, and vascular tone in large-caliber vessels decreased by 8% in the former patients. Conclusion: A one-month Vasavital course administered to patients with DR had a positive effect on the visual system function and ocular circulation parameters, which provides grounds for the use of the Ginkgo biloba-based preparation as a monotherapy or as part of a combined treatment for initial functional changes in the visual system in DR.